The Effect of SOLE (Self Organized Learning Environment) Model and Reading Interest on Writing Skills - Nadia Eka Putri Indriani; Syahrul Ramadhan (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study evaluates the effectiveness of the Self-Organized Learning Environment (SOLE) model in improving 10th-grade students' writing skills, compared to traditional teaching methods. The study addresses the gap in existing literature regarding how the SOLE model may enhance writing abilities, especially among students with varying levels of reading interest. The research is significant in its contribution to understanding the practical applications of SOLE in promoting critical thinking and independent learning. A quantitative experimental design was employed, involving 10th-grade students from SMAN 2 Padang during the 2024/2025 academic year. Data were collected through pre- and post-test assessments of students’ exposition text writing skills. Statistical analysis was performed to compare the outcomes between the experimental and control groups. The results indicated that students taught using the SOLE model demonstrated superior writing skills compared to those taught through traditional methods, regardless of their reading interest levels. The SOLE model had a particularly positive impact on both high and low reading interest students, though no significant interaction between the model and reading interest was found. These findings suggest that the SOLE model is an effective method for improving writing skills across diverse student populations. The study's implications point to the potential benefits of adopting the SOLE model in educational settings to promote independent learning and enhance writing instruction.